Human Resource Management (HRM) Training for Tobacco Entrepreneurs in Garut Regency - Sapril Mubarok, Teten Mohamad; Gustari, Tresna Dita; Nabila, Syifa Thahira; Padilah, Azka Muhammad (Fakultas Kewirausahaan Universitas Garut, 2025)
This community service activity aims to enhance the understanding and skills of tobacco processing industry players in Garut Regency in human resource management (HRM) as well as to encourage the downstream processing of tobacco products. The activity involved local tobacco entrepreneurs who face the challenge of low local absorption due to the dominance of raw tobacco sales to outside regions. The method applied was face-to-face training held at Kafe Kopi Jaya, Garut, which included lectures, interactive discussions, and Q&A sessions. The results indicate an improvement in participants’ knowledge of competency-based HRM strategies, the importance of a conducive work environment, and sustained managerial support. The conclusion of this activity is that well-structured and relevant HRM training can improve employee competence, productivity, and organizational commitment, thereby supporting the sustainability and competitiveness of the tobacco processing industry in Garut.